Ventral lateral and DN1 clock neurons mediate distinct properties of male sex drive rhythm in Drosophila. - Fujii, S.; Amrein, H. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Male sex drive rhythm (MSDR) in Drosophila is a circadian behavior only observed in the social context of male-female pairs. In the presence of a female, males exhibit long periods of courtship activity with a pronounced rest phase at dusk, although isolated males exhibit an activity peak at dusk. The molecular mechanisms regulating the switch between these activity patterns are unknown. Here, we genetically manipulate the molecular clock in different subsets of neurons and find that proper oscillation of the molecular clock in ventral lateral neurons is essential for MSDR. These neurons express pigment-dispersing factor, the lack of which disrupts MSDR. Furthermore, we show that a cluster of dorsal neurons (DN1s) requires the molecular clock to synchronize the trough phase at dusk in MSDR and to establish the evening peak in single fly locomotor rhythm (SLR). Finally, we provide evidence that DN1s exert their roles in MSDR and SLR via distinct signaling pathways.